EL CONFLICTO ARMADO EN COLOMBIA, UNA APROXIMACIÓN A SU IDENTIDAD ONTOLÓGICA : CASO DE LAS FARC - Robledo Fernández, Juan Carlos (Cuadernos de Administración, 2006)
This work, approaches the subject of the identity of the conflict from three fundamental angles, the first two coming from the theory of the rebellion that Paul Collier (investigator in the World Bank and the university of Oxford) has been developing and a third one from an application of structured analysis from the philosophical Rhombus proposed by Professor Ph.D Renée Bedar from the HEC of Motreal. The first undertaken model is the one of the Concupiscence or the rebellion motivated by the sacking, the greed, the avarice. In this section a general analysis is done formulating the concept of the success probability of a rebellious incursion, its relation with the Gross Rent and the Net Rent of the rebellious group, and, finally, the costs of the rebellious group in its incursions. Finally, are exposed the limitations of the rebellious group and the forces of defense of the government in relation to the eligible population to be incorporated to anyone of the two forces. The second analysed model is the one of “Complaint” or model of rebellion by the injustice. In this model one approaches the problematic of the political exclusion and the revenge, as well as the concept of the public imaginary for the accomplishment of the rebellious actions. There were also related the intervening variables from an abstract model of relation. Thirdly there’s an application made of the principles formulated by Renée Bedard from the Philosophical Rhombus and the four ways of being. There is an effort made in this section to characterize the ontology from the organization of the government’s forces of defense of and those of the rebellious group, in the same way is put in contrast an analysis of the individual that integates these organizations, under the scope of the ways of being. Finally, the conclusions and proposals are considered, and there is an annexed that shows a small photographic file about the conflict and it’s consequences.